Loss of CtIP disturbs homologous recombination repair and sensitizes breast cancer cells to PARP inhibitors - Wang, Junhui (Oncotarget, 2015)
Breast cancer is one of the leading causes of death worldwide, and therefore, new and improved approaches for the treatment of breast cancer are desperately needed. CtIP (RBBP8) is a multifunctional protein that is involved in various cellular functions, including transcription, DNA replication, DNA repair and the G1 and G2 cell cycle checkpoints. CtIP plays an important role in homologous recombination repair by interacting with tumor suppressor protein BRCA1. Here, we analyzed the expression profile of CtIP by data mining using published microarray data sets. We found that CtIP expression is frequently decreased in breast cancer patients, and the patient group with low-expressing CtIP mRNA is associated with a significantly lower survival rate. The knockdown of CtIP in breast cancer MCF7 cells reduced Rad51 foci numbers and enhanced f H2AX foci formation after f-irradiation, suggesting that deficiency of CtIP decreases homologous recombination repair and delays DNA double strand break repair. To explore the effect of CtIP on PARP inhibitor therapy for breast cancer, CtIP-depleted MCF7 cells were treated with PARP inhibitor olaparib (AZD2281) or veliparib (ABT-888). As in BRCA mutated cells, PARP inhibitors showed cytotoxicity to CtIP-depleted cells by preventing cells from repairing DNA damage, leading to decreased cell viability. Further, a xenograft tumor model in mice with MCF7 cells demonstrated significantly increased sensitivity towards PARP inhibition under CtIP deficiency. In summary, this study shows that low level of CtIP expression is associated with poor prognosis in breast cancer, and provides a rationale for establishing CtIP expression as a biomarker of PARP inhibitor response, and consequently offers novel therapeutic options for a significant subset of patients.